MANAJEMEN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI SEKOLAH DASAR ISLAM DI TULUNGAGUNG - Indayati, Retno (J-MPI (Jurnal Manajemen Pendidikan Islam), 2017)
Islamic elementary school is a based Islamic elementary education institution that gives students basic competencies to continue their study to the more higher level. Recently the society’s trust toward the school is getting increase. One of the factors affecting the increase of the society’s interest toward the Islamic elementary school is the quality of the teachers who have integrity, comitment and competencies. This research was intended to analyze and find out: 1) planning of Competence Based Human Resource Management in Islamic Elementary School; 2) developing strategies of Competence Based Human Resource Management in Islamic Elementary School; and 3) the effects of developing Competence Based Human Resource Management in Islamic Elementary School. This study used a qualitative approach by with multi-case study using multisite research design. The data were collected using in-depth interview, participant observation, and documentation. The results of this research revealed that: 1) planning of Human Resource in Islamic Elementary School is religious-based competency approach. The steps are: a) need analysis, b) the determination of the standard qualification of teachers (academic, religious, experience, motivation and ‘dakwah”); c) selection, with open system selection, d)apprenticeship and evaluation, include: competence, motivation and commitment of devotion. 2) Developing strategies of Competence Based Human Resource Management in Islamic Elementary School by synergizing the continuous training and development (CTD), performance evaluation and build a spirit of integration ‘dakwah’ and education. Goal of human resources development in the aspects of: a) improving the commitment and internship through giving compensation, career development, personal and family guidance, and building good cooperation ; b) improving academic and spiritual competence through training and socialization, supervisison, further studies, motivation that working is religious good deeds, praying together, and gettingclose to Allah (al qiyadah); 3) the effects of developing human resource were teachers have high motivation, they became models for the students, they are loyal and committed to serve and give attention to the students. From the findings above it can be concluded that the human resource management at Islamic elementary school is spirituality based human resource management.Key Words: Human Resource Management, based competence, Islamic Elementary School.